The influence of breast volume and age on the occurrence of severe forms of radiation dermatitis as a complication of postoperative 3D-conformal radiotherapy of the breast - one center experience - RADOJIČIĆ, BOJAN; Dolić, Mirko; Radojičić, Marija (PONS - medicinski časopis, 2024)
Introduction/goal. In the world, the incidence of breast cancer is constantly increasing, and according to the results of GLOBOCAN 2022, in the population of women, breast cancer is in the first place in terms of incidence and in the second place in terms of mortality. The modern approach to breast cancer treatment is multidisciplinary. Surgery, drugs and radiotherapy, as well as their combinations, are applied in the order that depends on the stage of the disease, general condition, comorbidities. The results of previous studies have proven that in selected patients with early breast cancer there is no statistically significant difference in overall survival between partial resection followed by radiation therapy and mastectomy, which rapidly increased the number of breast conserving surgery. In this regard, it is a challenge to carry out postoperative radiotherapy of the breast with as few consequences as possible for the surrounding organs (heart and lungs), but also to minimize early and late reactions of the skin as well as the breast itself and, accordingly, radiation dermatitis (RD) is the most common complication that occurs in patients treated with radiotherapy. The aim of the study was to determine whether breast volume and age have an influence on the occurrence of more severe forms of acute skin toxicity.Methods. The research was conducted at the Radiotherapy Department of the Radiology Institute of the Military Medical Academy in Belgrade, and the study had a retrospective-prospective character. The study included data analysis of 42 patients who were diagnosed with early breast cancer. After a breast conserving surgery was performed on them, with or without adjuvant chemotherapy, they were advised to undergo further treatment with postoperative radiation therapy.Results. All patients (100%) had a skin reaction. As treatment progressed and RD appeared or worsened, there was a tendency to increase in intensity of signs and symptoms. The percentage of mild forms of RD (gr I) was 52.4%, moderate (gr II) 35.7%, medium severe (gr III ) 11.9%, while there were no severe forms in the form of necrosis and ulceration. The average breast volume in RD grade I was 1542ml, grade II 1698ml, grade III 1988ml. The average age of subjects with acute RD grade I is 66 years, grade II 64 years and grade III 58 years.Conclusion. Using the 3D conformal technique, in local postoperative radiation therapy of the breast in the standard mode of fractionation in the supination position, breast volume and age have no statistical significance on the degree of acute skin toxicity.
Keywords: breast cancer, postoperative radiotherapy, skin toxicity, radiation dermatitis, moist desquamation